AUDIT TATA KELOLA TEKNOLOGI INFORMASI PADA SEKERTARIAT DAERAH OGAN ILIR MENGGUNAKAN FRAMEWORK COBIT 5 DOMAIN DSS(DELIVER,SERVICE, AND SUPPORT) - Sari, Indah Novita; Damayanti, Nita Rosa; yulianingsih, Evi; Oktarina, Tri (Jurnal Ilmiah Matrik, 2023)
The Regional Secretariat is an institution or organization that assists the Regent in formulating policies and coordinating administration regarding the implementation of Regional Apparatus duties and administrative services. People not only pay attention to quantity, but also quality. The same is true for other agencies or organizations. One way that can be done is to carry out an Information Technology Audit using the COBIT 5 Framework. By following the stages and criteria set by COBIT. These stages will produce a parameter for the level of management of information technology called Capability Level. Where these parameters will later be used as a benchmark by comparing them with the targets to be achieved. The difference between the target to be achieved and the curent situation is called Gap Analysis